Tomographic evaluation of the temporomandibular joint in malocclusion subjects: condylar morphology and position - Luciana Fonseca MERIGUE; Ana Cláudia de Castro Ferreira CONTI; Paula Vanessa Pedron OLTRAMARI-NAVARRO; Ricardo de Lima NAVARRO; Marcio Rodrigues de ALMEIDA (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract The aim of this study was to investigate condyle concentricity and morphology, and their association with Class I and II malocclusions (Angle). The sample consisted of 49 individuals of both genders, between 11 and 35 years old, divided into two groups, G1: 26 patients with Class I malocclusion, and G2: 23 patients with Class II malocclusion, selected for orthodontic treatment. Evaluation of the condyle morphology and position was performed by the same previously calibrated examiner using cone-beam computed tomography (CBCT) images of the subjects. The CBCT scans were analyzed by means of a 3D program (Dolphin 11.5, Dolphin Imaging & Management Solutions, Chatsworth, CA, USA), with a 25% level of sensitivity. The images obtained from the coronal slices were employed for the condyle morphology analysis, which classified the condyle form as rounded, as flat or convex, and as triangular or angled. The sagittal slices were used to classify further the condyles as concentric and displaced anteriorly or posteriorly. A clinical examination was also performed, including TMJ and muscle palpation. The kappa test was used to evaluate investigator calibration; the Chi-square and paired t-tests were used for analysis. The convex and anteriorly positioned condyles were found most frequently, regardless of the type of malocclusion. No association was observed between the groups regarding condylar characteristics.